Amplitude Controlled Adaptive Feedback Resonance in a Single Degree-of-Freedom Mass-Spring Mechanical System. (2016) - Malas, Anindya; Chatterjee, Shyamal
Abstract: Many mechanical and micro-mechanical applications utilize artificially generated self-excited oscillations either as the working principle or as the performance enhancer. The present paper investigates a switched damping adaptive feedback control method for inducing artificial controlled self-excited oscillation in a single degree-of-freedom damped mass-spring mechanical system. The adaptive feedback control can generate oscillation at the natural frequency of the system with controlled amplitude and maintain the frequency of oscillation at the natural frequency of the system under parametric variations. The desired amplitude of oscillation even under parametric variations can be achieved when the controller is designed utilizing a frequency detector (used to adapt the natural frequency of the system). Numerical simulations confirm the analytical results.